Accumulation of nutrients and radionuclides from plantation areas into lake sediment / Seh Datul Riduan Khalid - Khalid, Seh Datul Riduan (2013)
A nutrient is the important component for plant growth. Fertilizer is added into the soil to supply more nutrients for the plants. The excessive usage of fertilizer at plantation areas will lead to the nutrients loss through leaching and into catchment area carried by water from runoff. Cameron Highlands as study areas was chosen because of the excessive agriculture activity and the present of Lake of Sultan Abu Bakar Dam as catchment area. Soil samples were taken from two tea plantation (Bharat Tea Plantation and Boh Tea Plantation) and sediment was taken at Lake of Sultan Abu Bakar Dam. Nutrients and radionuclides content in soil and sediment were measured to determine the concentration, radiation hazard index and accumulation occur at tea plantation areas and Lake of Sultan Abu Bakar Dam. The measurements include the profile distribution in soil and sediment. Measurement of nutrients and radionuclides was carried out using CHNS analyzer, EDXRF and Gamma Af\ spectrometer. The nutrients (N, P and K) and radionuclides ( Ra, Ra, K, U and Th) at plantation B (Boh Tea Plantation) is higher than plantation A (Bharat Tea Plantation). N and P shows decreasing trends through the depth whereas K shows no observable trends in soil. In sediment, P and K show monotonic trends through the depth and N was not detected in sediment. Radionuclide does not show any observable trends through the depth in soil and sediment. The concentration range ofN at tea plantation areas is not detected - 3490 mg/kg for Plantation A and 400 - 9760 mg/kg for Plantation B. Concentration of P range from 596 - 2712 mg/kg for Plantation A and 591 - 7956 mg/kg for Plantation B. The concentration of K in soil is range from 922 - 10597 mg/kg for Plantation A and 3759 - 15846 mg/kg for Plantation B. In sediment P range from 1144 mg/kg - 1745 mg/kg and K is 10018 mg/kg - 17759 mg/kg. The concentration of N in sediment was not detected due to the low concentration. The activity concentration of radionuclides was measured using gamma spectrometer in soil and sediment. The range activity concentration for 226Ra is 44.76 - 86.31 Bq/kg for Plantation A and 70.20 - 142.89 Bq/kg for Plantation B. 228Ra is range from 77.04 - 195.53 Bq/kg for Plantation A and 157.12 - 280.11 Bq/kg for Plantation B. 40K range from 78.67 - 491.43 Bq/kg for Plantation A and for Plantation B is range from 192.08 - 628.84 Bq/kg respectively. The external hazard index (Hex) at plantation B is higher than one whereas plantation A below one but annual effective dose still in range proposed by UNSCEAR 2008 0.3-1.0 mSv/y. The accumulation of nutrients and radionuclides in sediment was calculated by estimation of sedimentation rate except for N that was not detected in sediment. The cluster analysis for nutrients and radionuclides for both plantation show different cluster group of elements. This may be due to the different of soil texture, pH, topography and origin of the elements.